RELATIONSHIP BETWEEN LAND COVER CHANGES AND THE SURFACE AREA OF LAKE RANAU - Naimullah, Muhammad; Dewi, Citra; Anisa, Rahma; Fadly, Romi (Forestry Study Program University Of Mataram, 2025)
Ranau Lake is one of Indonesia's 30 national priority lakes facing pressures from climate change and human activities, negatively impacting its water quality and ecosystem. This study aims to analyze land cover changes in the catchment area, measure the changes in the lake's surface area, and examine the relationship between land cover changes and Ranau Lake's surface area from 2016–2022. The data includes Sentinel-1A IW GRDH imagery, ESRI land cover maps, and Google Earth images. The analysis employed Support Vector Machine (SVM) classification, spatial analysis, and linear regression. The results reveal that water bodies, vegetation, and built-up land categories experienced an increase of 36.78 hectares, 33.96 hectares, and 9.1 hectares, respectively, while bare land decreased by 80.03 hectares. Ranau Lake's surface area increased by 28.3 hectares, showing a significant relationship between land cover changes in water bodies (R² = 99.88%), bare land (R² = 94.92%), vegetation (R² = 66.06%), and built-up land (R² = 56.85%) and the lake's surface area. These findings highlight the critical role of land cover changes in influencing the dynamics of lake surface area, an essential indicator of ecosystem health. This study emphasizes the importance of sustainable land cover management in supporting Ranau Lake's conservation. Continuous use of SAR-based remote sensing technology is recommended for land cover monitoring, enabling data-driven decision-making in water resource management.